2016
DOI: 10.1534/g3.116.031286
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic Prediction of Single Crosses in the Early Stages of a Maize Hybrid Breeding Pipeline

Abstract: Prediction of single-cross performance has been a major goal of plant breeders since the beginning of hybrid breeding. Recently, genomic prediction has shown to be a promising approach, but only limited studies have examined the accuracy of predicting single-cross performance. Moreover, no studies have examined the potential of predicting single crosses among random inbreds derived from a series of biparental families, which resembles the structure of germplasm comprising the initial stages of a hybrid maize b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
131
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(140 citation statements)
references
References 46 publications
7
131
1
1
Order By: Relevance
“…Therefore, increasing TP size will increase the precision of estimating GCA effects (Technow et al, 2014). Although the genetic covariance between inbreds was used for hybrid performance prediction in this study, recent research showed that applying genomic-estimated GCA and SCA might result in higher prediction accuracy when using T0 hybrids in the TP (Kadam et al, 2016). This heterotic pattern condition may be one explanation why prediction accuracy benefits more from increasing TP size using T2 hybrids than T0 hybrids.…”
Section: Prediction Accuracy Response To Increased Training Sizementioning
confidence: 92%
See 1 more Smart Citation
“…Therefore, increasing TP size will increase the precision of estimating GCA effects (Technow et al, 2014). Although the genetic covariance between inbreds was used for hybrid performance prediction in this study, recent research showed that applying genomic-estimated GCA and SCA might result in higher prediction accuracy when using T0 hybrids in the TP (Kadam et al, 2016). This heterotic pattern condition may be one explanation why prediction accuracy benefits more from increasing TP size using T2 hybrids than T0 hybrids.…”
Section: Prediction Accuracy Response To Increased Training Sizementioning
confidence: 92%
“…This heterotic pattern condition may be one explanation why prediction accuracy benefits more from increasing TP size using T2 hybrids than T0 hybrids. Although the genetic covariance between inbreds was used for hybrid performance prediction in this study, recent research showed that applying genomic-estimated GCA and SCA might result in higher prediction accuracy when using T0 hybrids in the TP (Kadam et al, 2016).…”
Section: Prediction Accuracy Response To Increased Training Sizementioning
confidence: 99%
“…These results 654 contrast with those from previous studies on hybrid maize, which showed low contribution of 655 non-additive genetic effects to genotypic variability. Critically, those studies were based on 656 panels derived solely from crosses between different heterotic groups, e.g., Flint×Dent (Technow 657 et al 2014, Giraud et al 2017 or SS×NSS (Kadam et al 2016). Therefore, complementation 658 effects were relatively consistent across hybrids, such that variability for specific combining 659 ability (contributed by dominance and/or epistasis) was low.…”
Section: Partition Of Polygenic Effects By Gene Proximity Increased Pmentioning
confidence: 99%
“…However, apart from gain per unit cost, GS still proved advantageous at lower values in cases, where lines do not produce enough seed for actual testcrossing, and when field testing is reduced due to resource constraints. It also increased efficiency in cross prediction, especially early on in breeding programs (Kadam et al, 2016). Likewise, under drought, GS proved highly effective in identifying parental hybrid combinations that increased genetic gain in maize hybrids (Beyene et al, 2015).…”
Section: Hybrid‐enabled Line Profiling (Help)mentioning
confidence: 99%